ACRL and Community College Libraries: We've Been Framed!. Issue 1 (2nd April 2016) - Craven, Heather
ABSTRACT: The change to the ACRL Framework from a set of standards that was created in 2000 has been the subject of much debate. The impact on community colleges is considered in this opinion piece.